Novel one-pot synthesis of 2-Aryl-4(3H)-quinazolinones using room temperature ionic liquid as reaction medium as well as promoter - Potewar, T. M.; Nadaf, R. N.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Synthetic Communications, 2005)
An efficient one-pot synthesis of 2-aryl-4(3H)-quinazolinones from 2-amino benzamides and substituted benzoyl chlorides in a room temperature ionic liquid is described. Compared with the classical reaction conditions, this new synthetic method has the advantages of recyclability of ionic liquid, very good to excellent yields (78-92%), the absence of hazardous and expensive catalysts, and easy workup procedures giving rise to a process with minimum waste.
Keywords: 2-amino benzamide; 2-aryl-4(3H)-quinazolinones; benzoyl chlorides; Ionic liquid